Equation of state of ultracold fermions in the 2D BEC-BCS crossover region - Böttcher, Igor; Bayha, Luca; Kedar, Dhruv; Murthy, Puneet A.; Neidig, Mathias; Ries, Martin Gerhard; Wenz, André Niklas; Zürn, Gerhard; Jochim, Selim; Enss, Tilman (Arxiv, 2016)
We report the experimental measurement of the equation of state of a two-dimensional Fermi gas with attractive s-wave interactions throughout the crossover from a weakly coupled Fermi gas to a Bose gas of tightly bound dimers as the interaction strength is varied. We demonstrate that interactions lead to a renormalization of the density of the Fermi gas by several orders of magnitude. We compare our data near the ground state and at finite temperature to predictions for both fermions and bosons from Quantum Monte Carlo simulations and Luttinger-Ward theory. Our results serve as input for investigations of close-to-equilibrium dynamics and transport in the two-dimensional system.
Gesehen am 23.11.2017